A systems biology approach identifies SART1 as a novel determinant of both 5-fluorouracil and SN38 drug resistance in colorectal cancer - Allen, Wendy L. (2011)
Chemotherapy response rates for advanced colorectal cancer remain disappointingly low, primarily due to drug resistance, so there is an urgent need to improve current treatment strategies. In order to identify novel determinants of resistance to the clinically relevant drugs 5-Fluorouracil (5-FU) and SN38 (the active metabolite of irinotecan), transcriptional profiling experiments were carried out on pre-treatment metastatic colorectal cancer biopsies and HCT116 parental and chemotherapy-resistant cell line models using a disease-specific DNA microarray. To enrich for potential chemo-resistance-determining genes, an unsupervised bioinformatics approach was employed, and 50 genes were selected and then functionally assessed using custom-designed siRNA screens. In the primary siRNA screen, silencing of 21 genes sensitised HCT116 cells to either 5-FU or SN38 treatment. Three genes (RAPGEF2, PTRF and SART1) were selected for further analysis in a panel of 7 CRC cell lines. Silencing SART1 sensitised all 7 cell lines to 5-FU treatment and 4/7 cell lines to SN38 treatment. However, silencing of RAPGEF2 or PTRF had no significant effect on 5-FU or SN38 sensitivity in the wider cell line panel. Further functional analysis of SART1 demonstrated that its silencing induced apoptosis that was caspase 8-dependent. Furthermore, silencing of SART1 led to a down-regulation of the caspase 8 inhibitor, c-FLIP, which we have previously demonstrated is a key determinant of drug resistance in colorectal cancer. This study demonstrates the power of systems biology approaches for identifying novel genes that regulate drug resistance and identifies SART1 as a previously unidentified regulator of c-FLIP and drug-induced activation of caspase 8.